Strophanthidin Attenuates MAPK, PI3K/AKT/mTOR, and Wnt/β-Catenin Signaling Pathways in Human Cancers - Reddy, Dhanasekhar; Ghosh, Preetam; Kumavath, Ranjith (Frontiers in Oncology, 2020)
Lung cancer is the most prevalent in cancer-related deaths while breast carcinoma is the second most dominant cancer in women accounting for the maximum number of deaths worldwide. Cancers are heterogeneous diseases that consist of several subtypes based on the presence or absence of hormone receptors and human epidermal growth factor receptor 2. Several drugs have been developed targeting cancer biomarkers nonetheless, their efficiency was not adequate due to the high re-emergence rate of cancers and fundamental or acquired resistance towards such drugs which leads to partial therapeutic possibilities. Recent studies on cardiac glycosides (CGs) positioned them as potent cytotoxic agents that target multiple pathways to initiate apoptosis and autophagic cell death in many cancers. In the present study, our aim is to identify the anti-cancer activity of a naturally available cardiac glycoside (Strophanthidin) in human breast (MCF-7), lung (A549), and liver cancer (HepG2) cells. Our results demonstrate a dose-dependent cytotoxic effect of Strophanthidin in MCF-7, A549, and HepG2 cells, which was further supported by DNA damage on drug treatment. Strophanthidin arrested the cell cycle at the G2/M phase; this effect was further validated by checking the inhibited expressions of checkpoint and cyclin-dependent kinases in Strophanthidin induced cells. Moreover, Strophanthidin inhibited the expression of several key proteins such as MEK1, PI3K, AKT, mTOR, Gsk3α, and β-catenin from MAPK, PI3K/AKT/mTOR, and Wnt/ β-catenin signaling. The current study adequately exhibits the role of Strophanthidin in modulating the expression of various key proteins involved in cell cycle arrest, apoptosis, and autophagic cell death. Our in silico studies revealed that Strophanthidin can interact with several key proteins from various pathways. Taken together, this study demonstrates the viability of Strophanthidin as a promising anticancer agent, which may serve as a new anticancer drug.